A method for exploring word‐colour associations. Issue 1 (30th September 2019) - Chen, Yun; Yang, Jie; Pan, Qianqian; Vazirian, Marjan; Westland, Stephen
Abstract: Strong associations exist between colours and concepts or words. Understanding these associations, sometimes referred to as colour emotions, is important for effective use of colour in art and design. Traditionally the relationships have been systematically explored in experiments where participants scale colours according to bipolar adjectives such as warm‐cool. In this article, a method for exploring the relationships between words and colours is suggested and is demonstrated. A psychophysical experiment is described where participants select colours based on words. The data are used to show that many similarities between the word‐colour relationships for UK and Chinese participants although some interesting differences are also revealed. The method makes explicit the observation that there is not a one‐to‐one relationship between words and colours. The method could be used to explore word‐colour relationship for specific words and participant groups or could be used to generate ground‐truth data for testing methods for automatically generating the word‐colour relationships.